The results of a comparative analysis of the population of the population of Ukraine and countries of the European region for HIV as a rationale for improving the pharmaceutical provision of patients with socially dangerous pathologies - Yefremova, Valeriia; Panfilova, Hanna; Lebedyn, Alla; Iurchenko, Gennadii; Oksana, Okseniuk; Vitaly, Chernukha; Lyubov, Tereshchenko; Inna, Chebernina (ScienceRise: Pharmaceutical Science, 2022)
The aim: to conduct a comparative analysis of HIV morbidity in Ukraine and in some countries of the European region over the years and to determine the characteristics of the epidemiological situation on this pathology. Materials and methods. The object of the study was HIV incidence data presented on the website of the WHO European Health Portal (1990–2018) and in the Annual Report of the European Center for Disease Prevention and Control and the WHO Regional Office for Europe on HIV/AIDS Surveillance in Europe (2010–2019). Historical, analytical-comparative, systemic, graphic, logical, hypothetical-deductive, mathematical-statistical, epidemiological and other research methods were used. Results. It is established that during 1990-2018 in the group of reference countries only for Ukraine and Belarus there was a significant fluctuation in the incidence rates presented in absolute data. In all countries except Romania, the number of HIV-infected in 2019 was higher than in 1990 (Ukraine, Belarus, Poland) and in 1993 (Germany). Analysis of the dynamics of the absolute number of HIV-infected persons by indicative years (1993, 1999, 2004, 2010, 2016, 2019) allows us to assert the different nature of changes in epidemiological data by group of reference countries. Only in Poland we saw a gradual increase in data for 1993-2019. In all other countries, there was a complex nature of changes in morbidity. According to the analysis of HIV incidence, presented in relative terms, it was found that they ranged in the largest range in Belarus, namely from 11.3 (2010) to 26.1 (2017). Belarus typically had the highest mean chain growth/decline rates of HIV incidence (1.09). In turn, the lowest value of these coefficients was observed in the EU as a whole (0.97). Comparison of average values of HIV incidence per 100 thousand population suggests that in Ukraine this figure was 1.85 times higher than in Belarus, 11.36 times higher than in Poland, 8.65 times higher than in Romania, 10.27 times higher than in Germany and 5.88 times more than in the EU group. Conclusions. The presence of a complex and tense epidemiological situation with HIV infection in Ukraine in comparison with other countries of the reference group of countries suggests the need to implement comprehensive programs to counter the spread of this socially dangerous infection and introduce models for the rational use of limited health care resources and international funds